Perosomus elumbis in a Holstein calf infected with bovine viral diarrhea virus - Karakaya, E.; Alpay, G.; Yilmazbas-Mecitoglu, G.; Alasonyalilar-Demirer, A.; Akgul, B.; Inan-Ozturkoglu, S.; Ozyigit, M. O.; Seyrek-Intas, D.; Seyrek-Intas, K.; Yesilbag, K.; Gumen, A.; Keskin, A. (Tierärztliche Praxis Ausgabe G: Großtiere / Nutztiere, 2013)
The detection of bovine viral diarrhea virus (BVDV) in a female Holstein calf presented with perosomus elumbis, a congenital anomaly, is reported here. A cow with dystocia was evaluated and an abnormal dead calf was detected during vaginal examination. The calf was retrieved via caesarean section and exhibited abnormalities characteristic of PE, such as vertebral and pelvic malformations. These abnormalities were further confirmed using radiographic and necropsy examinations. At necropsy cerebellar hypoplasia was an additional finding, which is a typical lesion associated with bovine virus diarrhea (BVD). Several tissue samples from the calf were tested for the presence of antigens of BVDV and bovine herpesvirus-1 (BHV-1) by ELISA. In addition, sera samples from the dam and calf were tested for the presence of antibodies against BVDV, BHV-1, and bluetongue disease virus (BTV) using a virus neutralization assay. Results indicated that the calf was congenitally infected with BVDV, whereas there was no evidence for the presence of BHV-1 and BTV. In the dam’s serum no antibodies against BVDV, BHV-1, and BTV were detected. Even though the etiology of perosomus elumbis is unknown, BVDV, which causes fetal anomalies at early gestation in cows, may have been a contributing factor in this case.
Keywords: Cattle; congenital malformations; Perosomus elumbis; bovine viral diarrhea virus